2019
DOI: 10.2147/ott.s205169
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiRNA-124 inhibits the proliferation, migration and invasion of cancer cell in hepatocellular carcinoma by downregulating lncRNA-UCA1</p>

Abstract: Purpose: It has been reported that miRNA-124 inhibits hepatocellular carcinoma (HCC) progression, while lncRNA-UCA1 promotes HCC. The aim of this study is to find whether miRNA-124, as a tumor suppressor in HCC can inhibit lncRNA-UCA1 in HCC cell. Methods: Tumor tissues and adjacent healthy tissues were obtained from 66 patients diagnosed with HCC in Binzhou Medical University Hospital from January 2011 to January 2013. Cell proliferation assay, in vitro cell migration and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…1 Hepatocellular carcinoma (HCC) is the predominant type of liver cancer and accounts for approximately 80% of liver cancer. 2 In the past decade, the incidence and mortality of HCC has shown an upward trend in both males and females. 3 Current treatment options for HCC patients include surgical resection, local ablation, and chemotherapy, and these have achieved certain therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hepatocellular carcinoma (HCC) is the predominant type of liver cancer and accounts for approximately 80% of liver cancer. 2 In the past decade, the incidence and mortality of HCC has shown an upward trend in both males and females. 3 Current treatment options for HCC patients include surgical resection, local ablation, and chemotherapy, and these have achieved certain therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…These lncRNAs were primarily associated with tumor grade, TNM stage, and lymphatic metastasis in HCC. Among these 26 lncRNAs, MCM3AP-AS1, UCA1, AKR7L, C3P1, AKR1C6P, LINC01018, and A1BG-AS1 have been reported in lymphatic metastasis and invasion and are diagnostic biomarkers for HCC (Praml, Savelyeva & Schwab, 2003;Wang et al, 2006;Zhang, Luo & Zhang, 2019;Zhao et al, 2019a;Zhao et al, 2019b;Zhao et al, 2019c;Zheng et al, 2015). However, other lncRNAs are not yet associated with HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Closely related dysregulated lncRNAs may assist in identifying valuable biomarkers for the diagnosis and prognosis of HCC. Current studies of HCC and lncRNAs have mainly focused on sequencing small tissue samples and cell lines (Tan et al, 2019;Zhao et al, 2019a;Zhao et al, 2019b;Zhao et al, 2019c). Large sample population studies are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence has demonstrated that dysregulated miRNAs play a crucial role in the initiation, progression, and therapy of various tumors [4,28,34]. Baolei et al revealed that miRNA-124 is a negative regulator of HCC with respect to proliferation and invasion by downregulating lncRNA-UCA1 [35]. Baltruskeviciene E et al found that downregulated expression of miRNA-148a and miRNA-625-3p is related to tumor budding in colorectal cancer, and EMT was considered a possible molecular mechanism [36].…”
Section: Discussionmentioning
confidence: 99%